2019
DOI: 10.1021/acs.jpcc.9b01531
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Optical, Electrochemical, DFT Studies, NLO Properties, and Ultrafast Excited State Dynamics of Carbazole-Induced Phthalocyanine Derivatives

Abstract: In this paper, we present results from the detailed investigations on the synthesis, optical, emission, electrochemical, and ultrafast nonlinear optical (NLO) properties along with the excited state dynamics of zinc­(II) 2,10,16,24-tetrakis­(9-phenyl-9H-carbazol-2-yl)­phthalocyanine (CBZPC1) and zinc­(II) 2,10,16,24-tetrakis­(4-(9H-carbazol-9-yl)­phenyl)­phthalocyanine (CBZPC2). Due to the presence of carbazole moieties, the Soret band was found to be broadened. The emission studies performed using different s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
55
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(59 citation statements)
references
References 67 publications
4
55
0
Order By: Relevance
“…The NLO behavior of rGO-based composites has been reported in the literature. 26,44 For example, Anand et al have investigated the NLO properties of hydrogen exfoliated graphene-Pd composites and reported a NLA coefficient of $ 4.9 Â 10 À4 cm GW À1 with fs excitation. 44 A study has shown a b value of $ 1.8 Â 10 À3 cm GW À1 in exfoliated graphene-CuO hybrid composites in the fs regime.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The NLO behavior of rGO-based composites has been reported in the literature. 26,44 For example, Anand et al have investigated the NLO properties of hydrogen exfoliated graphene-Pd composites and reported a NLA coefficient of $ 4.9 Â 10 À4 cm GW À1 with fs excitation. 44 A study has shown a b value of $ 1.8 Â 10 À3 cm GW À1 in exfoliated graphene-CuO hybrid composites in the fs regime.…”
Section: Resultsmentioning
confidence: 99%
“…24 The nonlinear optical (NLO) properties of GO, rGO and rGOnanomaterial composites have been considerably studied by the scientic community. [25][26][27] The nonlinear optical materials are widely being used in different areas like diversifying lasers, laser mode-lockers, advanced spectroscopy, information technology etc. 28 Pristine graphene with vanishingly small band gaps possesses only saturation absorption (SA).…”
Section: Introductionmentioning
confidence: 99%
“…In NLO applications, optical limiting is considered as an important phenomenon to permit the transmission of only low intensity radiation restricting the high intensity radiation. [ 55 ] In the measurements, the transmitted fluence is recorded with the input energy tuned using a neutral density filter. The optical limitation response of ABAQ crystal is depicted in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…All the details of the Z-scan experiments are documented in our earlier works. 46,47 The solutions were placed in a 1 mm cuvette (thickness was less than the Rayleigh range), satisfying the thin-sample approximation during the Z-scan data analysis. The input peak intensities used were 20-60 GW cm À2 and the Rayleigh range was in the 1.9-2.8 mm range for the 700-900 nm spectral window.…”
Section: Nonlinear Optical Studiesmentioning
confidence: 99%
“…[29][30][31][32][33][34][35] In this regard, our group has also investigated many phthalocyanines to understand the structure and NLO properties correlation for identifying potential molecules for various photonic applications. [36][37][38][39][40][41][42][43][44][45][46][47] over the last few years. To this end our group has been involved in investigating and optimizing the NLO properties of different phthalocyanine, Corrole 37 molecules in the form of thin lms, nanoparticles (NPs) and solutions.…”
Section: Introductionmentioning
confidence: 99%